Modelling pollutant movement / Kamaruddin Mohd Salleh - Mohd Salleh, Kamaruddin (1997)
A proper environmental resources investigation is an essential thrust in any development program to be sustainable for long term basis The specific strategies adopted may vary in terms of priorities and emphasis depending on the needs of the country but they should include the effective implementation of conservation program, pollution control legislation , environmental awareness and commitments through continuing education , land use planning , Environmental Impact Assessment procedures and research Basic to all these strategies is an effective monitoring and assessment system which could provide the :hni>t r,nd objcctivity ;n decision making processes either with respect to legislation's , Standard criteria of Environmental Impact Assessment, land use planning or identification of problem areas for further research A great deal of effort is being expended in improving numerica! modelling techniques and rapid developments in the field of numerical models and computer packages have been a feature of recent time The aim of this study is therefore to model pollutants movement by using one of the computer packages program called M1KE 21